A facile approach for the trifluoromethylthiolation of methylenecyclopropanes. Issue 1 (27th October 2016) - Chen, Min-Tao; Tang, Xiang-Ying; Shi, Min
Abstract : Trifluoromethylthiolation of methylenecyclopropanes (MCPs) has been developed by using AgSCF3 /Na2 S2 O8 as a trifluoromethylthiolation source (SCF3 ) to give trifluoromethylthiolated 1, 2-dihydronaphthalene derivatives in moderate to good yields. Abstract : A facile approach for the trifluoromethylthiolation of methylenecyclopropanes (MCPs) has been developed by using AgSCF3 /Na2 S2 O8 as a trifluoromethylthiolation source (SCF3 ) to give trifluoromethylthiolated 1, 2-dihydro-naphthalene derivatives in moderate to good yields, and the reaction has been proven to go through a radical-type pathway. The products can easily be aromatized upon oxidation, offering a new method for the construction of trifluoromethylthiolated naphthalenes.